Oral health effects of ecstasy (MDMA) and methamphetamine: a narrative review - Newell, Lily-Rose; Fouillen, Kevin-John; Orliaguet, Marie; Kichenin, Johanna; Boisramé, Sylvie (Frontiers in Oral Health, 2025)
This review aims to explore the impact of 3,4 methylenedioxymethamphetamine (MDMA), commonly known as ecstasy, on oral health, while also drawing comparisons with methamphetamine (MA) due to their pharmacological similarities and overlapping oral manifestations. MDMA is a psychostimulant derivative of amphetamine (AM) with empathogenic and hallucinogenic properties, widely consumed, especially among young adults. Its pharmacological effects lead to both acute and long-term systemic consequences. Among its oral manifestations, xerostomia is notably prevalent and strongly associated with increased intake of sugary beverages, contributing to heightened risks of carious lesions, tooth wear and periodontal disease. Bruxism and jaw clenching, frequent during MDMA use, are implicated in temporomandibular joint dysfunction and can lead to significant tooth wear lesions. This review also discusses periodontitis prevalence, often linked to poor oral hygiene, poly-drug use, and behavioral changes. Additionally, cases of soft tissue damage and unique patterns of decay have been documented. These findings highlight the need for dental professionals to recognize oral health issues associated with MDMA, MA and polydrug use.